Variations of risk factors for ischemic stroke and its subtypes in Chinese patients in Taiwan - Chung-Fen Tsai (Nature Portfolio, 2021)
Abstract Chinese have a higher stroke incidence and a different distribution of ischemic stroke (IS) subtypes as compared with Caucasians. Herein we aimed to investigate the prevalence and associations of major risk factors in IS and its subtypes in Chinese patients. From 2006 to 2011, we included 4953 acute IS patients consecutively recruited in National Taiwan University Hospital Stroke Registry (mean age 68 years; male 59%). For each risk factor, we accessed the proportion in all IS patients, and calculated odds ratios for each main IS subtype versus other subtypes. Multiple logistic regression models were used to adjust for confounders, and to examine the associations of risk factors with IS subtypes. Compared with other ischemic subtypes, large artery atherosclerotic and lacunar strokes were associated with hypertension, diabetes, and hyperlipidaemia, while cardioembolic strokes were associated with ischemic heart disease. Furthermore, the associations with hypertension and diabetes became stronger in lacunar strokes after adjusting for confounders, but not in other ischemic subtypes. Here we report the variable effects of risk factors on different IS subtypes in Chinese patients in Taiwan. Our findings could help shed light on different mechanisms of IS subtypes and provide targets to make more effective strategies for IS prevention.